How to perform transabdominal chorionic villus sampling: a practical guideline. (2nd May 2016) - Monni, Giovanni; Pagani, Giorgio; Stagnati, Valentina; Iuculano, Ambra; Ibba, Rosa Maria
Abstract: The spread of both first trimester screening for chromosomal abnormalities and the possibility to check for single gene disorders at DNA-analysis has increased the request for chorionic villus sampling (CVS) in the first trimester. In order to perform placental biopsy, two routes are possible: the transcervical (TC) and the transabdominal (TA). In early days, the trancervical technique was the most diffused, but since its introduction into clinical practice, the TA technique has become the approach of choice in detriment of the TC technique. In our institution, we have a 30-year experience in TA-CVS with more than 26 000 procedures performed. Considering the expertise and the volume of procedures undertaken at our unit, we suggest a practical guideline for novel operators in TA-CVS.